The Armed Forces in the proposal of a new Political Constitution for Chile - Cea Cienfuegos, Sergio; Herrera Aguayo, Claudio (Derecho Público Iberoamericano, 2022)
This academic work has as purpose to analyze the main rules of the proposal of a new Constitution for Chile related to the Armed Forces, their constitutional tasks, their link with the President of the Republic, as well as some general duties and rights that are reiterated specifically for these institutions.